Do Cash Flow and Accounting Profit Information Affect Stock Prices? (Study of Food & Beverage Companies on the Indonesia Stock Exchange) - Anik Yuliati; Indah Muniroh (JASF: Journal of Accounting and Strategic Finance, 2021)
This study aims to determine the effect of cash flow statement information and accounting profit on stock prices. The object of this research is a food & beverage sub-sector manufacturing company listed on the Indonesia Stock Exchange in 2015-2019. The sampling technique used a purposive sampling technique with ten samples of financial statements that meet the criteria. Theanalysis technique uses the help of Partial Lease Square (PLS) with SmartPLS 3.0 Software. The study results show that the Cash Flow Statement of operating and funding information does not affect stock prices. On the other hand, information on the investing Cash Flow Statement and accounting profit affect stock prices. The more investors intend to buy or keep shares; the stock price will increase. Vice versa, if the number of investors who intend to sell or release shares increases, the share price will decrease. Based on these results, it is suggested that investors in deciding on selling or buying stock shares may pay more attention to the information from investing cash flow and accounting profit.